Fisheries and aquaculture : the food security of the future - Agust Einarsson, 1952-; Oladottir, Asta Dis (Elsevier, 2021)
Fisheries and Aquaculture: The Food Security of the Future takes a multidisciplinary approach in evaluating the fisheries and aquaculture sectors from the scienti?c and practical perspectives of industry professionals. The authors recognize the importance of looking at the industry from a value chain viewpoint, not only for food security but also for a blue economy. The book takes a unique and innovative approach to show how?sheries and aquaculture can achieve sustainability and how small?shery communities can become highly successful?shery and aquaculture communities and contribute to overall industry globalization. This is a practical and useful reference for a wide-ranging audience. It is for those who wish to make systematic e?orts to develop their fisheries or aquaculture sectors, scientists and researchers, anyone in?sheries management or marine resource management,?sh farmers, policy makers, leaders and regulators, operations researchers, as well as faculty and students.